Safety evaluation of FAD2 RNAi transgenic Brassica napus L. based on microbial diversity and metabonomic analysis - Qi, Yanting; Wang, Qiming; Xie, Qingxuan; Wu, Chuan; Xu, Minhui; Han, Shaofan; Zhou, Ting; Li, Juan; Xia, Libing; Li, Wai chin; Pan, Weisong (Frontiers in Plant Science, 2022)
Oleic acid desaturase (FAD2) is the key enzyme that produces polyunsaturated fatty acids in rapeseed (Brassica napus L), which is one of the main oil crops. RNA interference (RNAi) is an emerging technique that provides new opportunities for the generation of new traits in plants. To increase oleic acid content and reduce linoleic and linolenic acid content in rapeseed, we constructed an ihpRNA plant expression vector of the FAD2 gene and obtained transgenic plants for multiple generations by stable inheritance. In this study, third-generation transgenic plants (T3), seventh-generation transgenic plants (T7), and wild-type plants (WT) were used. The differences in microbial community diversity between transgenic plants and wild-type plants and the up- and downregulation of rhizosphere metabolite contents were investigated. In conclusion, the results showed that the soil microbial community structure was stable, the general microbial community structure was not changed by the transgenic rhizosphere exudates, and no significant harmful root exudate of transgenic rapeseed on the environment was found through the microbial community and metabolomics analysis. This work may provide an understanding of the impact of RNAi on plant metabolites and a safety evaluation method for transgenic plants and a reference for rapeseed breeding.